Myelodysplastic Syndrome with t(1;7) Associated with Marked Dysmegakarypoiesis & Severe Thrombocytopenia: A Case Report and Review of the Literature - Michael Gilbertson (Case Reports in Hematology, 2012)
We present the case of a 70-year-old woman who had a bone marrow examination performed to investigate marked thrombocytopenia in the context of a recent history of metastatic glucagonoma. Surprisingly this identified marked dysmegakaryopoiesis and fulfilled diagnostic criteria for refractory cytopenia with multilineage dysplasia, with a relatively uncommon associated cytogenetic lesion t(1;7). We present the case and review the literature of this cytogenetic lesion.